KAJIAN EKSPERIMENTAL KERUNTUHAN TEKAN BENDA UJI BETON SELF COMPACTING CONCRETE - Immanuel Panusunan Tua Panggabean; Charles Harry Siregar (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2019)
Concrete test materials received in the field were treated and tested at the age of 28 (twenty eight) days, regulated in the Indonesian National Standard for concrete with the standard number SNI 2847: 2013. In addition, the equally important standard to be observed in concrete testing, especially in construction, is the observation of the shape of the collapse of the test object, which was written in the SNI 1974: 2011 concrete regulation. This collapse model needs to be considered because it can pay attention to the possibility of errors in testing. The test object used in this study was formed using Self Compacting Concrete type concrete. This type of concrete is an innovative concrete that does not require vibration for compaction. Because this concrete can flow by itself and actually fill the formwork until it reaches full compaction. These concrete collapse models must be considered because they are very interesting to see. Researchers conducted experiments on concrete collapse models made using several variations of concrete mixtures, ranging from variations in water content (standard, -5%, -10%, + 5%, + 10%), height variation of the test object (15 cm , 12.5 cm, 10 cm, 8.5 cm, 7.5 cm), and variation in age of the plan. From the research conducted by researchers, the number of specimens carried out shows the pattern of collapse of the crack model parallel to the upright axis, then there is the model of cone and shear failure and the least is the cone and split failure model.